Molecular mechanisms and genetic improvement of low‐phosphorus tolerance in rice. (17th October 2022) - Lu, Hong; Wang, Fei; Wang, Yan; Lin, Rongbin; Wang, Zhiye; Mao, Chuanzao
Abstract: Phosphorus (P) is a macronutrient required for plant growth and reproduction. Orthophosphate (Pi), the preferred P form for plant uptake, is easily fixed in the soil, making it unavailable to plants. Limited phosphate rock resources, low phosphate fertilizer use efficiency and high demands for green agriculture production make it important to clarify the molecular mechanisms underlying plant responses to P deficiency and to improve plant phosphate efficiency in crops. Over the past 20 years, tremendous progress has been made in understanding the regulatory mechanisms of the plant P starvation response. Here, we systematically review current research on the mechanisms of Pi acquisition, transport and distribution from the rhizosphere to the shoot; Pi redistribution and reuse during reproductive growth; and the molecular mechanisms of arbuscular mycorrhizal symbiosis in rice ( Oryza sativa L.) under Pi deficiency. Furthermore, we discuss several strategies for boosting P utilization efficiency and yield in rice. Summary: We systematically review current research on the mechanisms of Pi acquisition, transport and distribution from the rhizosphere to the shoot; Pi redistribution and reuse during reproductive growth; the molecular mechanisms of arbuscular mycorrhizal symbiosis in rice (Oryza sativa L.) under Pi deficiency; and the practical strategies for genetic improvement of the phosphorus use efficiency in rice.